El “escándalo Magnasco”. Denuncia pública y controversias sobre el papel del Congreso en la Argentina del 1900 - Romero, Ana Leonor (Anuario de Historia de América Latina, 2019)
This article analyzes the role of scandals as mechanisms for contesting the political power in Argentina at the turn of the century. As political satire in the previous years, the scandal was a way of denouncing the political system, emphasizing what was conceived a violation of social norms by individual politicians in the eyes of the public. During the second administration of Julio A. Roca, the public debate made use of this type of critique and interventions that aimed at different branches of the government. In particular, the text analyzes the accusation of corruption against the Ministry Minister of Justice and Public Instruction Osvaldo Magnasco in June of 1901. Through this case, the article examines how the definition of the politician´s moral character affected the forms of contesting the political system. Also, it considers the ways in which public opinion perceived the role played by legislative and executive power.